Intrauterine infection/inflammation during pregnancy and offspring brain damages: Possible mechanisms involved - Golan Hava; Huleihel Mahmoud; Hallak Mordechai (BMC, 2004)
Abstract Intrauterine infection is considered as one of the major maternal insults during pregnancy. Intrauterine infection during pregnancy could lead to brain damage of the developmental fetus and offspring. Effects on the fetal, newborn, and adult central nervous system (CNS) may include signs of neurological problems, developmental abnormalities and delays, and intellectual deficits. However, the mechanisms or pathophysiology that leads to permanent brain damage during development are complex and not fully understood. This damage may affect morphogenic and behavioral phenotypes of the developed offspring, and that mice brain damage could be mediated through a final common pathway, which includes over-stimulation of excitatory amino acid receptor, over-production of vascularization/angiogenesis, pro-inflammatory cytokines, neurotrophic factors and apoptotic-inducing factors.